An exploration of psychological trauma and positive adaptation in adults with congenital heart disease during the COVID-19 pandemic - Liza Morton; Calum Calderwood; Nicola Cogan; Claire Murphy; Evan Nix; Jacek Kolacz (The Beryl Institute, 2022)
The growing population of adults with congenital heart disease (CHD) often have lifelong experience of dealing with potentially traumatic health crises and medical uncertainty whilst facing increased vulnerability to post-traumatic stress disorder (PTSD). The COVID-19 pandemic presents additional challenges for this population including increased risk of health complications, shielding and strict social distancing, changes to medical care provision and social stigma. Despite such challenges, adults with CHD have the potential to also experience positive changes, yet little is known as to what helps cultivate positive adaptation and post-traumatic growth (PTG) within this context. The current study comprised a cross-sectional, anonymous, online study exploring psychosocial measures of traumatic experiences as well as protective factors that mitigate the risks to the mental health of adults with CHD (n=236) during the pandemic. Closed and open-ended questions and a series of standardised psychosocial measures of traumatic experiences, coping mechanisms, emotional regulation and PTG were used. Findings suggest the CHD population are at increased risk of PTSD which may be exacerbated by the COVID-19 pandemic. However, positive adaptation may promote post traumatic growth. In particular, emotional regulation is associated with post-traumatic growth. We recommend a growth-focused, psychologically and trauma-informed approach to medicine and public health, recognising the importance of supporting mental health and promoting living well with CHD during the COVID-19 pandemic and beyond. These findings are likely generalisable to other lifelong health conditions and shielding populations. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.